The Influence of the Seasonal Variability of Candida spp. Bloodstream Infections and Antifungal Treatment: A Mediterranean Pilot Study - Paola Di Carlo; Nicola Serra; Ornella Collotta; Claudia Colomba; Alberto Firenze; Luigi Aprea; Salvatore Antonino Distefano; Andrea Cortegiani; Giovanni Giammanco; Teresa Maria Assunta Fasciana; Roberta Virruso; Angela Capuano; et al. (Antibiotics)
Background/Objectives: Various factors associated with seasonality, including temperature, humidity, geographical composition, and seasonal fluctuations, can influence the trends of microbes responsible for hospital infections, such as Candida spp. This study evaluates the seasonal variability of Candida spp. bloodstream infections and antifungal resistance in hospitalized patients in Sicily. Methods: We retrospectively analyzed the demographic and epidemiological characteristics of 175 patients with blood cultures positive for Candida spp. Who were hospitalized at University Hospital Paolo Giaccone (A.U.O.P.), University of Palermo, Italy, from 1 January 2022 to 31 December 2024. Data on Candida species and antifungal resistance were also collected from the hospital’s database system to prevent and control hospital infections in A.U.O.P. Results: A total of 175 patients, 57.7% males, with a mean age of 68.3 years, were included in this study. Candida parapsilosis, Candida albicans, and Candida glabrata were more frequent in ICU (54.5%, p = 0.0001), medical (72.5%, p = 0.0003), and surgical settings (24%, p = 0.0161), respectively. C. parapsilosis was more frequent in dead patients (53.2%, p = 0.005). Among the seasons, we observed a significantly higher presence of C. glabrata in Autumn (20%, p = 0.0436). From the analysis of the seasons, C. parapsilosis and C. albicans were more frequent for each season, except in Spring, where the most frequent isolates were C. glabrata (5.1%, p = 0.0237) and C. parapsilosis (9.7%, p < 0.0001). The antifungal with the most resistance to Candida spp. was fluconazole in all seasons. Conclusions: Our study highlights the seasonal trends in Candida spp. and antifungal resistance, emphasizing climate change’s challenges on fungal diseases. These findings may contribute to improving prevention and treatment strategies for candidemia.